State of art of news values (second part) - Seixas, Lia (2025)
This article is the second in a series of papers on the state of the art of news value studies in Brazil and around the world. In this text, a sequel to the previous one, we identify the most relevant authors and articles for 'news values', 'news factors' and 'newsworthiness' in the Scopus, Web of Science and Scielo databases over the last 10 years. We compared the propositions and notions of the most followed authors in Brazil with 10 of the first key authors in foreign journals. We analyzed four concepts: news value, news factor, newsworthiness criteria and newsworthiness in Brazilian and foreign literature. In the end, it is understood that news value consists of 'journalistic doxa' (Schultz, 2007) for the characteristics of events, i.e. it is part of the knowledge that circulates in journalistic practices. On the other hand, newsworthiness is formed in society, the result of collective but influenced by individual interests. We also advocate stabilizing the concept of the news factor in undergraduate journalism schools.